A Digest of the Acts of Assembly, and the Ordinances, of the Commissioners and Inhabitants of the Kensington District of the Northern Liberties: for the Government of that District, at 45-47, Gunpowder § 2 (1832) - (:unkn) unknown (My University, 1787)
No person shall keep in any house, store, shop, cellar or other place within the city of Philadelphia, nor the country adjacent, within two miles of the said city, any greater quantity of gunpowder, at one time, than thirty pounds weight thereof, under the penalty of forfeiture of the whole quantity so over and above stored or kept, together with the sum of twenty pounds for every such offense
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER